2002
DOI: 10.1016/s1010-7940(02)00406-2
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the trachea and bronchus – a clinicopathologic study with DNA flow cytometric analysis and oncogene expression

Abstract: Complete surgical resection may provide best survival for tracheobronchial ACC. The DNA ploidy and SPF may correlate with tumor grading or metastasis. The overexpressions of HER-2/neu, p53 and COX-2 may impact the prognosis in patients with stage I non-small cell lung cancer, but did not express difference in our patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
1
9
1
Order By: Relevance
“…Although an equal sex distribution was noted previously [17,18] , recent literature shows male predominance, as was seen in our series [3,19] . AdCC spreads commonly by direct extension, perineural invasion, or haematogenous metastasis, whereas lymph nodal metastasis is uncommon [20] .…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Although an equal sex distribution was noted previously [17,18] , recent literature shows male predominance, as was seen in our series [3,19] . AdCC spreads commonly by direct extension, perineural invasion, or haematogenous metastasis, whereas lymph nodal metastasis is uncommon [20] .…”
Section: Discussionsupporting
confidence: 61%
“…Patients with AdCC of the LRT often present with cough, dyspnea, wheezing, or stridor, and are treated for upper respiratory tract infection or asthma for months before being diagnosed [17] .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that ploidy changes may play a role in the pathogenesis and the development of many different clinicopathological features of the neoplasms, but the actual mechanisms have not exactly determined and may be different in accordance with the organs and the cyto -and histopathological subtypes 14,15) . We performed a comparative study on the presence or the absence of the chromosomal aneuploidy in 28 cases of ADC with BAC pattern, 7 cases of benign lung diseases and 9 normal lung tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…Grade I ACCs are comprised primarily of a glandular or cystic pattern, and show essentially no evidence of solid growth; grade II tumors show less than 30% solid growth; and grade III tumors exhibit solid growth in more than 30% of the tumor volume. 10,17,18 Although some studies in salivary gland ACC have shown a relationship between the histologic grade and subsequent prognosis, 17,19 -22 these findings have not always been supported in subsequent studies. 23,24 In ACCL, similar controversy exists, with some studies showing prognostic importance of the histologic grade, 2,4,10 whereas others found that histologic grade failed to predict clinical outcome reliably.…”
Section: Histologic Featuresmentioning
confidence: 99%
“…Affected patients are usually adults, with one study reporting patients ranging in age from 29 to 79 years (mean, 54 years), and with a fairly equal occurrence in men and women. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Adenoid cystic carcinoma of lung (ACCL) is usually centrally located in the trachea or proximal bronchi, and therefore patients typically present with signs and symptoms of bronchial obstruction or ulceration, including dyspnea, cough, wheezing, pneumonia, and/or hemoptysis. Peripherally located ACCL may be asymptomatic and is less common, 5,13 constituting only 10 to 15% of all ACCLs.…”
Section: Clinical Featuresmentioning
confidence: 99%